Peripheral nerve control of metabolism and inflammation - Ting Liu (2025)
The regulation of inflammatory and metabolic pathways in adipose and liver tissues is complex, involving various cellular mechanisms and molecular pathways1-3. It has been demonstrated that the cholinergic vagus nerve, through its efferent branch, regulates inflammatory and anti-inflammatory cytokine release to maintain homeostasis in the spleen and beyond4,5. However, much remains to be explored on the role of cholinergic signaling in specific organs such as liver and adipose tissue homeostasis.Over recent decades, there has been a multitude of impactful discoveries on neural regulation of inflammation and metabolism4,6,7, but we are only at the beginning of understanding the detailed mechanisms of how neural reflexes regulate organ function. This thesis explores aspects of this biology in the liver and adipose tissue with the aim of providing additional insights that ultimately can help improve tools for disease diagnosis, prevention, and treatment of inflammatory and metabolic diseases such as metabolic dysfunction-associated steatotic liver disease (MASLD) and certain adipose tissue dysfunction. Studies over the last thirty years have shown that the central and peripheral nervous systems, along with the immune and metabolic systems, collaboratively regulate inflammation and metabolism4,6,8-10. The vagus nerve is one of the systems that have been widely studied in this context and found to be important in regulating inflammation and metabolism5,11,12. The work in this thesis builds on these studies and aims to further improve the understanding of neural regulation of inflammation and metabolism in liver and adipose tissue.In project I, we found that statin therapy in individuals with metabolic syndrome was associated with increased Patatin-like phospholipase domain-containing 3 (PNPLA3) and liver transcriptional changes linked to worse metabolic control. The observations underscore the importance of considering the implications on liver pathophysiology of lipid-lowering therapy in patients with the metabolic syndrome, including the need for improved mechanistic understanding of the regulation of liver inflammation and metabolism in this patient group.In project II, we investigated the role of the vagus nerve in acute liver inflammation, particularly its effect on the key cells in the development of metabolism- associated steatohepatitis, hepatic stellate cells.In project III, we summarized the available literature on the role of cholinergic signaling in adipose tissue.In project IV, we studied the mechanisms of vagus nerve control of weight loss and adipose tissue physiology in this context and discovered a new role for neutrophils in vagotomy-mediated weight loss.This thesis improves our understanding of the physiological effects of vagus nerve signals in the context of inflammation and metabolism. The observation that a loss of vagus nerve signals affects hepatic stellate cell activity and the discovery of a link between the vagus nerve, neutrophils, and weight loss provide a new perspective on the neural regulation of fatty liver disease and weight loss. The insights certainly encourage further studies on cholinergic control of inflammation and metabolism and suggest a potential for neuro-immune interventions in the regulation of fat turnover and body weight.List of scientific papersI. Ahmed, O., Shavva, V. S., Tarnawski, L., Dai, W., Borg, F., Olofsson, V. V., Liu, T., Saliba-Gustafsson, P., Simini, C., Pedrelli, M., Bergman, O., Norata, G. D., Parini, P., Franco-Cereceda, A., Eriksson, P., Malin, S. G., Björck, H. M., & Olofsson, P. S. (2025). Statin-associated regulation of hepatic PNPLA3 in patients without known liver disease. Journal of internal medicine, 297(1), 47-59.https://doi.org/10.1111/joim.20032II. Ahmed, O., Caravaca, A. S., Crespo, M., Dai, W., Liu, T., Guo, Q., Leiva, M., Sabio, G., Shavva, V. S., Malin, S. G., & Olofsson, P. S. (2023). Hepatic stellate cell activation markers are regulated by the vagus nerve in systemic inflammation. Bioelectronic medicine, 9(1), 6.https://doi.org/10.1186/s42234-023-00108-3III. Shavva, V. S., Tarnawski, L., Liu, T., Ahmed, O., Olofsson, P. S. (2024). Cholinergic signaling in adipose tissue. Current Opinion in Endocrine and Metabolic Research. 37. 100546.https://doi.org/10.1016/j.coemr.2024.100546IV. Liu T., Caravaca A.S., Cai M., Mendes P., Dai W., Vacquie J.J., Guo Q., Zhang Y., Schipper R., Simón R.R., Pei S., Karlsson M., Shavva V.S., Hagberg C.E., Tarnawski L .* , Olofsson P.S .* A lymphocyte antigen 6G-dependent mechanism regulates hormone-sensitive lipase phosphorylation in white adipose tissue. [Manuscript]